Competencies and training needs of agriculture extension officers in develop the MADA’s paddy farming - Man, Norsida (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
Muda Agriculture Development Authority (MADA) is the government organizations that involve totally in agriculture. The functions of this agency were to promote, stimulate, facilitate and undertake economic and social development in main granary areas. The primary goal of this area is to increase the incomes of farmers by improving their productivity in paddy farming. The second goal is to increase the output of paddy to fulfill the national requirements. If every extension programme in this area is well developed and succeed, perhaps the two goals can be reached. Basically, the success of these extension programmes is depends on the extension agents and the extension programme itself. The role of the agriculture extension agents in the context to adopt new technologies demands Extension Agents’ competencies. The research questions are: 1) What is the level of competency of the extension agents in MADA; and 2) how do extension agents performance, contribute to the success of extension program? The purpose of this study was to identify the competencies of MADA’s extension agents and their training needs. The specific objectives of this study are: 1) To identify the respondents’ profiles; 2) To determine the competency of extension agents in MADA; 3) To determine extension agent skills and ability in performing their job and their training needs. The respondents competencies in every aspect of their job was determined as 1) Extension Agent as Change Agent; 2) Planner; 3) Leader; and 4) Agriculture Expert and it’s importancy to their job as extension Agent.